Congelare tutto il reale. Il problema della negazione nell’interpretazione deleuzeana del masochismo. - Alessio Calabrese (Kaiak, 2018)
This paper aims to explore the meaning of Deleuze’s interpretation of masochism. This work focuses on the concept of dénegation of the worldly reality, which describes the distance between two different types of cold. Masochistic fantasy is in fact irreducible to the sadistic one. This study attempts therefore to demonstrate, by discussing some main ideas of the Freudian psychoanalysis, how the Deleuzian’s reading of Sacher-Masoch romances constitutes a first experiment to think the positivity of desire through and the Oedipus.